Lymph Node Metastasis after a Soft Tissue Sarcoma of the Leg: A Case Report and a Review of the Literature. (6th February 2013) - Nelen, S. D.; Vogelaar, F. J.; Gilissen, F.; Van der Linden, J. C.; Bosscha, K.
Abstract : Introduction . Soft tissue sarcomas (STSs) represent 1 percent of all adult malignancies and sarcomas only rarely spread to the regional lymph nodes. Case Presentation . We present a case of a woman with a dermatofibrosarcoma protuberans and a sarcoma not therwise specified of the lower extremity. The patient had no distant metastasis during follow-up, but did develop a regional lymph nodemetastasis (RLNM) in the groin. We reviewed the literature about RLNM in STSs. Discussion . Reviewing the literature we see that within specific histological types RLNM occurs as often as distant metastasis. Furthermore RLNM occurs in over 10% for specific histological types and in 24% of all patients with a soft tissue sarcoma of the lower extremity. Except for radical lymphadenectomy with a 5-year survival rate of 46% there is no appropriate treatment. Conclusion . The risk for a RLNM in certain histological types and anatomical locations might transcend the risk for a distant lung metastasis.